Dynamic Mechanical Behavior of Dry and Water Saturated Igneous Rock with Acoustic Emission Monitoring - Jun Guo; Guo-rui Feng; Ting-ye Qi; Pengfei Wang; Jian Yang; Zhen Li; Jinwen Bai; Xianjie Du; Zehua Wang (Shock and Vibration)
The uniaxial cyclic loading tests have been conducted to study the mechanical behavior of dry and water saturated igneous rock with acoustic emission (AE) monitoring. The igneous rock samples are dried, naturally immersed, and boiled to get specimens with different water contents for the testing. The mineral compositions and the microstructures of the dry and water saturated igneous rock are also presented. The dry specimens present higher strength, fewer strains, and rapid increase of AE count subjected to the cyclic loading, which reflects the hard and brittle behavior and strong burst proneness of igneous rock. The water saturated specimens have lower peak strength, more accumulated strains, and increase of AE count during the cyclic loading. The damage of the igneous rocks with different water contents has been identified by the Felicity Ratio Analysis. The cyclic loading and unloading increase the dislocation between the mineral aggregates and the water-rock interactions further break the adhesion of the clay minerals, which jointly promote the inner damage of the igneous rock. The results suggest that the groundwater can reduce the burst proneness of the igneous rock but increase the potential support failure of the surrounding rock in igneous invading area. In addition, the results inspire the fact that the water injection method is feasible for softening the igneous rock and for preventing the dynamic disasters within the roadways and working faces located in the igneous intrusion area.